Mineralogical control on the magnetic anisotropy of lavas and ignimbrites: a case study in the Caviahue-Copahue field (Argentina) - Moncinhatto, Thiago Ribas (2019)
Fil: Moncinhatto, Thiago R. Universidade de Sao Paulo. Instituto de Astronomia, Geofısica e Ciências Atmosféricas. São Paulo, Brazil.